The Dilemma of Human Security on Palm Oil Plantation in Indonesia - Ardiyanti, Dwi; Anwar, Ahmad (Universitas Muhammadiyah Yogyakarta, 2018)
Palm oil plantation has proven to have contributions in increasing Indonesian wealth and economy. The fact that Indonesia becoming the biggest palm oil exporter in the world promises a higher expectation for Indonesia’s economic growth. Meanwhile, this national economic source generates controversies for the environment, health, and social issues besides its advantages. This article discusses the problem caused by palm oil plantation in Indonesia and how it is dilemmatic to human security concept. Palm oil plantation offered affordable and an easy access to material for mass exported products for daily need. The phenomena then become destructive when it comes to political interest related to ecological survival, economic boosting program, health for surrounding communities, and another field in human security issue. This study does not only show the fact that palm oil plantation is needed for the sake of economic growth and national development, but also analyse how economic demand may destruct another aspect of human security. The numerous impacts for long-term economic and development made it crucial to be analysed. While there are many studies about dilemma on human security, yet, only a few studies on palm oil plantation and its progress in Indonesia. This paper seeks to broaden the related literature.